Acne and Stress: Impact of Catecholamines on Cutibacterium acnes - Borrel, Valérie; Thomas, Pauline; Catovic, Chloé; Racine, Pierre-Jean; Konto-Ghiorghi, Yoan; Lefeuvre, Luc; Duclairoir-Poc, Cécile; Zouboulis, Christos C.; Feuilloley, Marc G. J. (Frontiers in Medicine, 2019)
Cutibacterium acnes (former Propionibacterium acnes), is a bacterium characterized by high genomic variability with four subtypes and six major ribotypes. Skin is the largest neuroendocrine organ of the human body and many cutaneous hormones and neurohormones can modulate bacterial physiology. In the present study, we investigated the effect of catecholamines, i.e. epinephrine (Epi) and norepinephrine (Nepi), on two representative strains of C. acnes whose genome was fully sequence, identified as RT4 acneic and RT6 non-acneic strains. Epi and Nepi (10-6 M) had no impact on the growth of C. acnes but, as measured by the crystal violet technique, Epi increased RT4 and RT6 biofilm formation whereas Nepi was only active on the RT4 strain. Same results were obtained by confocal microscopy with the RT4 strain whereas no effect of both catecholamines was found on the RT6 strain. However, as shown by MATs tests, this strain is also sensitive to catecholamines since Epi and Nepi affect its surface polarity. Flow cytometry studies revealed that Epi and Nepi are unable to induce major changes of the bacterial surface properties and membrane integrity. As investigated by exposure of sebocytes to control or catecholamines treated bacteria, Epi and Nepi were without effect on the cytotoxicity and inflammatory potential of both C. acnes but stimulated their effect on sebocytes lipids synthesis. As Uriage spring thermal water was previously shown inhibiting biofilm production by C. acnes, its effect was tested after exposure of the bacteria to Epi and Nepi. The effect of thermal water on the response of C. acnes to catecholamines was depending of the surface where the biofilm was grown. The effect of catecholamines on C. acnes was completed by an in silico study which revealed the presence in the genome of C. acnes of a protein showing homology with the catecholamine receptor of Escherichia coli and eukaryotes. This study suggests that C. acnes should play a role of relay between stress mediators (catecholamines) and acne.